Restricted Bargaining for Organizations with Multiple Objectives - Contini, Bruno; Zionts, Stanley (Econometrica, 1968)
In this paper we show that a bargaining game will yield a negotiated solution with certain reasonable properties if the rules of the game are appropriately restricted. The basic idea is to provide an incentive for all the components to engage in a process of concessions until the point where some agreement is reached. The incentive consists of the threat of a preannounced imposed solution which will be enforced if no settlement can be reached. ORGANIZATIONAL DECISION MAKING is characterized by a multiplicity of partially conflicting objectives, all of which are desirable to some extent. Although the presence of multiple goal structures has been recognized for a long time in economic theory, the assumption of a unique goal of profit maximization has been made in nearly every analytical study of firm behavior, except in a few recent contributions.2 There are many reasons for this apparent lack of interest in the problem of multiple objectives and the failure to introduce them explicitly in models of firm behavior, though most of these are probably related to the difficulty of handling such objectives in a satisfactory way. For instance, a utility-if one exists-will generally fail to be a scalar function; more often it will be a multidimensional function.3 Furthermore, one must face the problem of aggregating the preferences of individual members into a group ordering which satisfies certain reasonable requirements.4 Several approaches have been developed to deal with the problem of resource allocation under multiple objectives; however, none are really satisfactory. Such